Characterization of the complete mitochondrial genome of Japanagallia spinosa and Durgades nigropicta (Hemiptera: Cicadellidae: Megophthalminae). (October 2017) - Wang, Jiajia; Dai, Renhuai; Li, Hu; Zhan, Hongping
Abstract: In this study, we determined and analyzed the complete mitochondrial genomes (mitogenomes) of Japanagallia spinosa and Durgades nigropicta (Hemiptera: Megophthalminae). The circular genome were 15, 655 bp long in J. spinosa (GenBank: KY123686) and 15, 974 bp long in D. nigropicta (GenBank: KY123687). The J. spinosa and D. nigropicta mitogenomes both contained 37 genes and the gene order was similar to that in other leafhoppers. All of the protein-coding genes started with ATN. In the J. spinosa mitogenome, the nad3, nad4L, and cytb genes used TAG as a stop codon, the atp8 and nad1 genes used TGA, and the cox2 gene used a single T. However, in the D. nigropicta mitogenome, three genes used a single T as the stop codon, whereas the nad3 gene used TAG. We predicted the secondary structures of the rRNAs in J. spinosa and D. nigropicta . The secondary structure of rrnL comprised six domains (domain III is absent in arthropods) with 42 helices and that of rrnS comprised three structural domains with 26 helices. Comparisons of J. spinosa and D. nigropicta detected some differences in H577 and H673. We determined the structural organization of the control regions in the mitogenomes of leafhoppers, where three types of repeat regions were found in most. The phylogenetic relationships between J. spinosa and D. nigropicta with related lineages were reconstructed using Bayesian inference and maximum likelihood analyses. The monophyly of each superfamily considered in this study was confirmed by the clades in the phylogenetic tree. And in this study, Cicadellidae was resolved as monophyletic by the phylogenetic analysis. This mitogenome information for J. spinosa and D. nigropicta could facilitate future studies of mitogenomic diversity and the evolution of related insect lineages.